“Cavalgar sem sela”: ensinamentos, demandas e incitações do currículo bareback em oposição às normas do uso do preservativo - Danilo Araujo de Oliveira (2021)
In this thesis, I analyze the functioning of the bareback curriculum in the production of truths, knowledge and subject positions. Bareback is an intentional sexual practice, typical of men who have sex with other men (MSM), of not using condoms during sex with casual and/or anonymous partners, constituting a practice of premeditation and eroticization of anal sex without condom. Considering its diffusion imbricated with cyberculture, based on works in the field of Cultural Studies, in its post-critical aspect, I name a set of heterogeneous sayings about the practice located in cyberspace, specifically in a blog and three profiles on Twitter, as a bareback curriculum. Curriculum, in turn, is understood as discourse, that is, as productive practices of power-knowledge that take place under specific emergency conditions. As a methodology, the research articulated elements and procedures of netnography and discursive analysis inspired by Foucault. I develop here the thesis that, in the functioning of the bareback curriculum, a process of subjectivation and the production of truths is engendered and prominently characterized by challenges and resistance to the prescribed norms of the mandatory use of condoms in sexual relations between men who do sex with men. Compounding these challenges and resistances is the dispute over sexual pleasure. Thus, it is stated in this curriculum that the most exciting, best and most pleasurable sexual act is the one that can be felt without a condom. This statement that emerges in this curriculum as truth establishes relationships with risk, pleasure, health and gender that affect the production of particular subject positions and different modes of conduction. In this way, the bareback curriculum works to produce different, complementary and conflicting subject positions: unrubberman, preper, bugchaser and giftgivers. With regard to the functioning of this curriculum, pornography is located as a technology integrated by the pedagogies of masculinization and eroticism, which operate with specific techniques to produce bareback as a transgressive practice linked to masculinity and the violation of the norm of mandatory use of condoms.